The No Child Left Behind Act and the legacy of federal aid to education. - Anderson, Lee W. (Education Policy Analysis Archives, 2005)
The No Child Left Behind Act of 2001 (NCLB) builds on a tradition of gradually increasing federal involvement in the nation's public school systems. NCLB both resembles and differs from earlier federal education laws. Over the past five decades, conservatives in Congress softened their objections to the principle of federal aid to schools and liberals downplayed fears about the unintended consequences of increased federal involvement. The belief in limited federal involvement in education has been replaced by the presumption by many legislators that past federal investments justify imposing high stakes accountability requirements on schools.